Values of tepo seliro in Bakri Syahid’s Tafsir al-Huda and Bisri Mustofa’s Tafsir al-Ibriz - Mubasirun Mubasirun (IAIN Salatiga, 2021)
Tafsir al-Huda and Tafsir al-Ibriz are religious narratives containing Javanese cultural values that aspire to live in peace and harmony. One of the means for achieving such aspiration is Tepo Seliro, which embodies values of tolerance, mutual respect, accepting differences, not blaming others, and not imposing one’s will on others. The current study aims to reveal the Javanese cultural values of Tepo Seliro in Tafsir al-Huda and al-Ibriz. The method of analysis used in the present research was content analysis with Gadamer’s hermeneutic approach, which is of the view that the reading and understanding of a text are essentially a dialog between the text, the author, and the world of the readers. The study results indicate that the lofty values inherent within the culture of Tepo Seliro are found in the al-Huda and al-Ibriz Quranic exegeses. Tafsir al-Huda tends to be more contextual in its elaborations of Tepo Seliro values, while Bisri Mustofa in Tafsir al-Ibriz frequently used terminologies that are less precise to indicate their true meanings.